Successful peace implementation: plans and processes. (2nd January 2016) - Lyons, Terrence
Abstract: All peace agreements are flawed, to varying degrees, because mistrustful parties sign under pressure to end humanitarian suffering. They generally include what they can, leave out what cannot be settled, and gloss over differences in an effort to stop the killing. The peace implementation process, however, sometimes provides opportunities to strengthen weak agreements so that the peace process is strengthened from its initial, imperfect state. This article argues that peace implementation is more likely to lead to sustained peace if the process is flexible and prioritises the demilitarisation of politics. Implementation that follows a strict blueprint and prioritises making deadlines and milestones articulated in the agreement are likely to freeze in place the mal-distribution of power at the time the fighting stopped and consequently make sustainable peace more difficult.